ENGINEERING THE FUTURE: INTEGRATING ENERGY-SAVING - Long, Chen Xiao; Min, Wang Lei (Research Journal of Engineering and Allied Sciences, 2024)
In the context of modern society, economic and technological progress, energy consumption is increasingly intensifying. It is in this context that people's understanding of energy conservation has gradually deepened, and control technologies for energy conservation have also rapidly developed. The energy-saving control system is a control system established based on energy-saving control technology. It utilizes programmable automation control technology to achieve automatic control of the system, and has obvious advantages in energy-saving control in electronic and mechanical engineering. This article takes the energy-saving controller of asynchronous motors for vehicles as the research object, with the aim of reducing motor energy consumption and improving motor efficiency, to study extending the range of electric vehicles. In the energy-saving comparison experiment, this article proposes a scheme for energy-saving control experiment of automotive asynchronous motors. The experimental results show that under energy-saving conditions, the power factor improvement in condition 2 is the largest, with a value of 67%. Under the condition of not using any energy, the power factor of condition 6 increases by a maximum of 65%. This proves the correctness and effectiveness of this control method. It is very important to adopt energy-saving control technology for the application research of asynchronous motors.